آليات الإقناع في القرآن الكريم: دراسة لنماذج لغوية وبلاغية مختار - حاقة, عبد الكريم (جامعة الوادي - University of Eloued, 2022)
ملخص: استعمل القرآن الكريم آليات لإقناع المخاطبين، وفي هذه الورقة البحثية حاولنا الإجابة عن السؤال الآتي: ما الآليات اللغوية والبلاغية التي استعملها القرآن الكريم لتحقيق مقصدية الإقناع، وكيف تم توظيف هذه الآليات؟ وقد جاءت الورقة في مقدمة وتوطئة وأربعة مباحث: كان الأول عن دعوة القرآن إلى التفكر واستعمال العقل. والثاني عن الخطاب القرآني والإقناع أما الثالث فعن المصطلحات التي استعملها القرآن الكريم للدلالة على الإقناع، ثم تناولنا في الرابع جملة من الآليات اللغوية والبلاغية التي استعملها القرآن الكريم في الإقناع، وفي الأخير جاءت الخاتمة متضمنة نتائج البحث ومن أهمها أن الخطاب القرآني خطاب إقناع يدعو إلى استعمال الحجج والبراهين بعيدا عن طرائق الإكراه والقسر، وقد توسل القرآن الكريم لتحقيق الإقناع بجملة من الآليات اللغوية والبلاغية كالتعليل والشرط والقسم والاستعارة والتمثيل وغيرها. Abstract: The Holy Qur’an used mechanisms to persuade the addressees, and in this research paper we tried to answer the following question: What are the linguistic and rhetorical mechanisms that the Holy Qur’an used to achieve the purpose of persuasion, and how were these mechanisms employed? The paper came in an introduction, a preface, and four topics: The first was about the Qur’an’s call to contemplation and the use of reason. The second is about the Qur’anic discourse and persuasion. The third is about the terms used by the Holy Qur’an to denote persuasion. Then we dealt in the fourth with a set of linguistic and rhetorical mechanisms that the Holy Qur’an used in persuasion. Finally, the conclusion came, including the results of the research, the most important of which is that the Qur’anic discourse is a discourse of persuasion that calls for the use of arguments and proofs away from the methods of coercion and coercion
The mechanisms of persuasion in the Holy Qur’an - a study of selected linguistic and rhetorical models -
مقال
Keywords: القرآن الكريم ؛ الخطاب ؛ الآليات ؛ الإقناع ؛ البلاغة; The Noble Qur’an ; Discourse ; Mechanisms ; Persuasion ; Rhetoric.